The Monetary Reforms of the Romans and the Finds of Roman Denarii in Eastern and Northern Europe - Lennart Lind (Current Swedish Archaeology, 1993)
Monetary measures undertaken inside the Roman Empire might be responsible for the composition of finds of Roman coins made ontside the Empire. A possible link between the composition of the denarius finds in Barbarian Europe, on the one hand, and the monetary reforms of Nero (54—68) and Septimius Severus (193—211), on the other hand, has long been recognised. There is however a third Roman monetary reform which has put its imprint on the denorius finds in Central, Eastern and Northern Europe, the one of Domitian (81—96).